THE MUTUAL SOLUBILITIES OF WATER WITH SUPERCRITICAL AND LIQUID CARBON-DIOXIDE - KING, MB; MUBARAK, A; KIM, JD; BOTT, TR (PRA PRESS, 1992)
New data are presented for. phase compositions and phase densities at 15, 20, 25, 35, and 40-degrees-C which extend the coverage of the classic work of Wiebe and Gaddy on the CO2/H2O system in this region. The pressure range extends to a little over 200 bar. The mutual solubilities of CO2 and water in the above range are very low and the data were collated by applying Raoult's law, expressed in terms of fugacity, to the solvent component in each phase, while applying Henry's law (with a pressure-dependent coefficient) to the other component. Henry's coefficient for water in the carbon dioxide-rich phase was obtained from the Redlich-Kwong equation. The method gives a good representation of the data in the fitted region and enables predictions and extrapolations to be made over a more substantial pressure range (1 to 500 bar). Water is frequently extracted alongside the components of primary interest in near-critical extraction operations with CO2 as solvent and the above data, and their collation, should be of interest in this regard.
Keywords: EQUATION; STATE